PEDAGOGICAL EDUCATION AND THE DEVELOPMENT OF RESEARCH COMPETENCIES THROUGH A MULTI-STAGE ASSESSMENT MODEL - Rustamova Shokhista Omonjonovna (International Scientific and Current Research Conferences, 2025)
In contemporary pedagogical education, the cultivation of research competencies among pre-service teachers represents a critical dimension of professional development. This study investigates the efficacy of a multi-stage assessment model in enhancing the analytical, methodological, and reflective capacities of learners engaged in pedagogical training programs. By integrating formative, summative, and self-assessment components, the proposed model facilitates continuous feedback loops that enable students to progressively refine their research skills, critical thinking, and evidence-based pedagogical decision-making.